Thermal stability of SPD-processed aluminum alloys - Internal friction as an indication for recovery, recrystallization and abnormal grain growth - Christian Illgen; Benjamin Bohne; Martin F.-X. Wagner; Philipp Frint (Journal of Materials Research and Technology, 2022)
In this study, we investigate the effect of different microstructures generated by severe plastic deformation on the thermal stability of an age-hardenable Al–Mg–Si alloy (AA6082). To analyze recovery and recrystallization we investigate the internal friction at various excitation frequencies and the microstructural evolution of the material in a wide range of temperatures. Severely deformed conditions of the alloy show a distinct increase of internal friction and a pronounced reduction of the materials hardness at elevated temperatures. Microstructural investigations reveal that different stages of recovery and recrystallization take place during the heating process. In a certain case, a remarkable correlation between frequency-dependent internal friction and abnormal grain growth in the microstructure is found. It is derived that internal friction measurements help to characterize the thermal stability of SPD processed materials. Since thermally-induced microstructural changes are directly related to changes of internal friction, these measurements help to identify characteristic temperatures of recovery, recrystallization and abnormal grain growth.